ANALISIS PENINGKATAN KEPUTUSAN KUNJUNGAN WISATAWAN MELALUI PROMOSI, PRASARANA DAN PELAYANAN - Imaduddin Imaduddin; Budiandriani Budiandriani; Andi Faisal Bahari (AkMen JURNAL ILMIAH, 2021)
This study aims to determine the effect of promotion, infrastructure and services on the decision to visit Seruni Beach tourism in Bantaeng Regency. This research approach uses a quantitative approach. With the sample used, amounting to 100 samples with predetermined criteria. And then the data analysis model used is multiple linear regression analysis processed using SPSS. Based on the results of the research conducted, it shows that simultaneously promotion, infrastructure and services together have an effect on tourist visit decisions. Then partially the quality of promotion has an effect on tourist visits, while the quality of infrastructure and services has no effect on tourist visit decisions.